2022
DOI: 10.1038/s41598-022-14819-1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study demonstrating the impact of surgical bowel preparation on intestinal microbiota composition following colon and rectal surgery

Abstract: The intestinal microbiota has been implicated in the pathogenesis of complications following colorectal surgery, yet perioperative changes in gut microbiome composition are poorly understood. The objective of this study was to characterize the perioperative gut microbiome in patients undergoing colonoscopy and colorectal surgery and determine factors influencing its composition. Using Illumina amplicon sequencing coupled with targeted metabolomics, we characterized the fecal microbiota in: (A) patients (n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…While some studies report short term alterations of the intestinal microbiome (19)(20)(21), Drago et al ( 16) demonstrated significant and persisting changes regarding the abundance of different bacterial phyla after bowel preparation followed by colonoscopy. The bowel preparation decreased the abundance of Firmicutes, especially Lactobacilli which have a health-promoting effect, whereas Proteobacteria abundance is increased (16,22,23). In addition to the luminal microbiome, it has been shown that standard bowel cleansing adversely affects the mucosaassociated microbiota (24).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies report short term alterations of the intestinal microbiome (19)(20)(21), Drago et al ( 16) demonstrated significant and persisting changes regarding the abundance of different bacterial phyla after bowel preparation followed by colonoscopy. The bowel preparation decreased the abundance of Firmicutes, especially Lactobacilli which have a health-promoting effect, whereas Proteobacteria abundance is increased (16,22,23). In addition to the luminal microbiome, it has been shown that standard bowel cleansing adversely affects the mucosaassociated microbiota (24).…”
Section: Introductionmentioning
confidence: 99%
“…To better characterize the mechanism of bowel preparation, our group recently published a longitudinal pilot study investigating the impact of MBP versus combined MBP þ OA on compositional changes in the intestinal microbiota of patients undergoing colonoscopy (MBP only) or colon surgery (preoperative MBP þ OA). 38 Patients in the colonoscopy/MBP only cohort had minimal compositional shifts in their microbiome with rapid return to baseline, whereas those in the surgery/MBP þ OA group demonstrated decreased α diversity, larger shifts in composition that persisted for an average of 1 month, and increased abundances of Streptococcus, Enterococcus, and Lactobacillus. 38 Further study is underway to investigate the association of these microbial changes in the setting of bowel preparation with anastomotic leak.…”
Section: Effect Of Preoperative Bowel Preparation On Surgical Infecti...mentioning
confidence: 92%
“…38 Patients in the colonoscopy/MBP only cohort had minimal compositional shifts in their microbiome with rapid return to baseline, whereas those in the surgery/MBP þ OA group demonstrated decreased α diversity, larger shifts in composition that persisted for an average of 1 month, and increased abundances of Streptococcus, Enterococcus, and Lactobacillus. 38 Further study is underway to investigate the association of these microbial changes in the setting of bowel preparation with anastomotic leak. Ultimately, the compositional shifts caused by nonspecific microbial killing, as seen with current bowel preparation regimens, may adversely affect anastomotic healing.…”
Section: Effect Of Preoperative Bowel Preparation On Surgical Infecti...mentioning
confidence: 92%
“…The impact of the bowel preparation method itself on gut microbiota composition is still under question, with reports often not reaching consensus due to various reasons including lack of analytical depth (Nagata et al, 2019). A recent report highlights minor shifts in gut microbial composition in non-surgical patients undergoing MBP, but a substantial impact of MBP combined with oral antibiotics (neomycin) in the gut microbiota of surgery patients, with compositional changes persisting in the early postoperative period, with a later repopulation to baseline (Nalluri-Butz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%